The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s0102-261x2007000500002
|View full text |Cite
|
Sign up to set email alerts
|

Sismografia rasa da plataforma continental de Cabo Frio - Araruama - RJ

Abstract: ABSTRACT. Seismic sections on the continental shelf adjacent to Araruama lagoon, Rio de Janeiro state, allowed the mapping of the acoustic basement and the seismic analysis of the sedimentary cover until the middle continental shelf (∼ 110 m). The acoustic basement outcrops in the northwest sector of the study area, while it is buried under 200 m of the sediments in the southeast sector (middle shelf). Four seismic sequences (SI, SII, SIII and SIV) limited by four unconformities (DI, DII, DIII and DIV) were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…INHG: Initiation of Norther Hemisphere Glaciations, MPT: Mid-Pleistocene Transition; MBE : Mid Brunhes Event; MIS Marine Isotopic Stage. The relationship between Late Quaternary margins' stratigraphy and sea level changes is well-documented from high resolution seismic data over the world, especially for the last few 100 kacycles (e.g., Kolla et al, 2000;Schuur Duncan et al, 2000;Liu et al, 2004;Rabineau et al, 2005Rabineau et al, , 2006Berne et al, 2007;Ridente et al, 2008;Bassetti et al, 2008;Tesson et al, 2010;Le Roy et al, 2014;Lafosse et al, 2018). Several studies have been conducted on the continental shelf of Rio de Janeiro State (e.g., Pinheiro-Moreira et al, 2001;Artusi et al, 2007;Fleming et al, 2009;Maia et al, 2010;Reis et al, 2013) and suggested that the continental shelf of the Santos Basin also offers the opportunity to examine the relationship between the architecture of the Quaternary deposits and the 100 ka glacio-eustatic cycles. However, all these studies focused on the continental shelf and could not describe the evolution of the sedimentary bodies towards the basin.…”
Section: Introductionmentioning
confidence: 99%
“…INHG: Initiation of Norther Hemisphere Glaciations, MPT: Mid-Pleistocene Transition; MBE : Mid Brunhes Event; MIS Marine Isotopic Stage. The relationship between Late Quaternary margins' stratigraphy and sea level changes is well-documented from high resolution seismic data over the world, especially for the last few 100 kacycles (e.g., Kolla et al, 2000;Schuur Duncan et al, 2000;Liu et al, 2004;Rabineau et al, 2005Rabineau et al, , 2006Berne et al, 2007;Ridente et al, 2008;Bassetti et al, 2008;Tesson et al, 2010;Le Roy et al, 2014;Lafosse et al, 2018). Several studies have been conducted on the continental shelf of Rio de Janeiro State (e.g., Pinheiro-Moreira et al, 2001;Artusi et al, 2007;Fleming et al, 2009;Maia et al, 2010;Reis et al, 2013) and suggested that the continental shelf of the Santos Basin also offers the opportunity to examine the relationship between the architecture of the Quaternary deposits and the 100 ka glacio-eustatic cycles. However, all these studies focused on the continental shelf and could not describe the evolution of the sedimentary bodies towards the basin.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies dealing with the Quaternary section have focused on the shelf morphology, superficial or subsurface sediment distribution or on the geomorphology and stratigraphic evolution of coastal features, like bays, coastal plains and the shallow shelf environments during the Holocene (e.g. COSTA, 1979;MAIA et al, 1984;MUEHE, 1989;MUEHE;CARVALHO, 1993;MUEHE;VALENTINI, 1998;TURCQ et al, 1999;MARTIN et al, 2003;ARTUSI;FIGUEIREDO, 2007;MAHIQUES et al, 2007;FLEMING et al, 2009). Therefore, the PlioQuaternary stratigraphic window remains as an important gap in the attempt to reconstruct the sedimentary history of the Santos basin continental shelf and of the Brazilian continental margin, as a whole.…”
Section: Introductionmentioning
confidence: 99%